Climatology and Characteristics of Medium‐Scale F Region Ionospheric Plasma Irregularities Observed by COSMIC Radio Occultation Receivers. Issue 10 (4th October 2018) - Watson, C.; Pedatella, N. M.
Abstract: Medium‐scale ionospheric ionization structures are a persistent global feature of the Earth's ionosphere. Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) radio occultation measurements are well suited to address the incomplete global observational picture of plasma density irregularities, including the global climatology in both bottomside and topside F region layers, and their structure in the vertical dimension. A climatological database of F region ionospheric irregularities and their characteristics has been developed through detection of total electron content perturbations by Global Positioning System receivers onboard COSMIC satellites. This paper presents global occurrence rates and detailed characteristics of equatorial to midlatitude medium‐scale irregularities under quiet geomagnetic conditions. The study covers 4 years, two during solar minimum (2008–2009) and two during the ascending phase of solar cycle 24 (2012–2013). Irregularities were found to occur frequently at high latitudes and during nighttime in equatorial to midlatitude regions in both bottom and topside F region layers. Longitudinal‐seasonal occurrence trends at equatorial and midlatitudes are consistent with previous irregularity climatology, which reaffirms that localized enhancements in plasma instability growth rates contribute to irregularity occurrence. Seasonal occurrence patterns also indicate a high occurrence of irregularities in regions corresponding to the solar terminator, confined primarily to altitudes below 300 km. The local time‐altitude distributions of equatorial and midlatitude irregularity occurrence, amplitude, and scale size provide further insight into irregularity generation mechanisms, and include features consistent with "spread F " irregularities and traveling ionospheric disturbances. Key Points: COSMIC radio occultation TEC measurements are used to examine the global climatology of medium‐scale ionospheric plasma irregularities Observation of vertical irregularity structure and distribution provides new insight into irregularity occurrence and characteristics Irregularities are persistently observed in nighttime equatorial to midlatitude regions, near the solar terminator, and at high latitudes